Conference report: The 14th congress of the International Society of Developmental and Comparative Immunology. (July 2019) - Abernath, Kelsey; Banach, Maureen; Barela Hudgell, Megan A.; Blackmon, Laura E.; Breaux, Breanna; Brusch, George A.; Criscitiello, Michael F.; Deiss, Thaddeus C.; Ding, Yang; Flowers, Emily; Kenney, Eric; Matz, Hanover; et al.
Highlights: 14th Congress of the International Society of Developmental and Comparative Immunology was held in Santa Fe New Mexico. Multiple parallel oral sessions, four plenary talks, and two poster sessions brought together diverse immunologists. Workshops covered origins and evolution of immunity, mentoring, communications and women in STEM. Purnima Bhanot of the NSF discussed funding opportunities in the IOS: Symbiosis, Defense and Self-recognition program. Society founder and historian Edwin Cooper lectured and signed his book.